The impact of varicocele repairon conventional semen paramaeters in infertile men: A meta-analysis using pre- and post-operative data. - Agarwal, Ashok; Cannarella, Rossella; Shah, Rupin; Boitrelle, Florence; Gül, Murat; Salvio, Gianmaria; Russo, Giorgio Ivan; Arafa, Mohamed; Saleh, Ramadan (Elsevier Science Inc., 2022)
Objective Varicocele is a widespread disorder affecting about 15% of the normal male population, 25% of men with abnormal semen analysis, and 35-40% of primary infertile men. There are few systematic reviews and meta-analyses (SRMAs) employing the “before-after” varicocele repair (VR) to assess the effect of VR on conventional sperm parameters. Indeed, the pregnancy rate is the most common outcome chosen by SRMAs on VR. The present SRMA aims to evaluate the impact of varicocele repair on conventional semen parameters in infertile patients with clinical varicocele using a before-after analysis. Materials and Methods Literature search was performed using Scopus, PubMed, Ovid, Embase and Cochrane databases following the Population Intervention Comparison Outcomes (PICO) model [Population: Infertile patients with clinical varicocele; Intervention: Varicocele repair; Comparison: Before-after parameters; Outcomes: semen volume, sperm concentration, total sperm count, total motile sperm count (TMSC), progressive sperm motility, total sperm motility, and sperm vitality]. Both randomized-controlled trials (RCTs) and observational studies were included. Results From the 1632 abstracts assessed for eligibility, 553 studies were finally included, with a total of 38,639 infertile men. The analysis showed a significantly higher semen volume [standardized mean difference (SMD) 0.20 (95% CI: 0.13, 0.28); n= 11391 before vs. 11616 after VR; p<0.01; I 2 =83.6%], sperm concentration [SMD 1.59 (95% CI: 1.47, 1.71); n= 37.899 before vs. 38639 after VR; p<0.01; I 2 =97.9%], total sperm count [SMD 1.82 (95% CI: 1.53, 2.12); n= 6239 before vs. 6360 after VR; p<0.01; I 2 =97.9%], TMSC [SMD 1.64 (95% CI: 1.31, 1.97); n= 7649 before vs. 7848 after VR; p<0.01; I 2 =98.7%], progressive sperm motility [SMD 1.85% (95% CI: 1.54, 2.15); n= 12812 before vs. 12935 after VR; p<0.01; I 2 =99.0%], total sperm motility [SMD 1.61% (95% CI: 1.47, 1.76); n= 25916 before vs. 26094 after VR; p<0.01; I 2 =98.0%], normal morphology [SMD 1.07% (95% CI: 0.92, 1.21); n= 23684 before vs. 24006 after parameters; p<0.01; I 2 =97.9%] and a lower sperm vitality [SMD -1.31 (95% CI: -2.11, 0.51); n= 1211 before vs. 1294 after VR; p<0.01; I 2 =98.5%] following varicocele repair compared to pre-treatment values.
Keywords: Infertile Men; Conventional Semen Paramaeters; Post-Operative Data